2023
DOI: 10.3389/fphys.2023.1060666
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system and cardiac neuro-signaling pathway modulation in cardiovascular disorders and Alzheimer’s disease

Abstract: The heart is a functional syncytium controlled by a delicate and sophisticated balance ensured by the tight coordination of its several cell subpopulations. Accordingly, cardiomyocytes together with the surrounding microenvironment participate in the heart tissue homeostasis. In the right atrium, the sinoatrial nodal cells regulate the cardiac impulse propagation through cardiomyocytes, thus ensuring the maintenance of the electric network in the heart tissue. Notably, the central nervous system (CNS) modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 368 publications
0
12
0
Order By: Relevance
“…The malfunctioning CANS is heavily remodeled in cardiac diseases such as myocardial ischemia, myocardial infarction, heart failure, and arrhythmias (Francis and Cohn, 1986 ; Tjeerdsma et al, 2001 ; Campelo and Abreu-Lima, 2004 ; Piepoli and Capucci, 2007 ; Hoyer et al, 2008 ; Kardesoglu et al, 2011 ; Phillips, 2012 ; van Bilsen et al, 2017 ; Ali et al, 2018 ; Hadaya and Ardell, 2020 ; Elia and Fossati, 2023 ; Kumar et al, 2023 ). The CPNS is capable of modulating the entire state of the CANS through both direct and indirect afferent pathway modulation that is transmitted to multiple levels of the CANS.…”
Section: Discussionmentioning
confidence: 99%
“…The malfunctioning CANS is heavily remodeled in cardiac diseases such as myocardial ischemia, myocardial infarction, heart failure, and arrhythmias (Francis and Cohn, 1986 ; Tjeerdsma et al, 2001 ; Campelo and Abreu-Lima, 2004 ; Piepoli and Capucci, 2007 ; Hoyer et al, 2008 ; Kardesoglu et al, 2011 ; Phillips, 2012 ; van Bilsen et al, 2017 ; Ali et al, 2018 ; Hadaya and Ardell, 2020 ; Elia and Fossati, 2023 ; Kumar et al, 2023 ). The CPNS is capable of modulating the entire state of the CANS through both direct and indirect afferent pathway modulation that is transmitted to multiple levels of the CANS.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophic factors are critical for neuronal survival as they promote neuronal proliferation, survival, and differentiation [ 117 ]. Neurotrophic factors regulate a variety of neurological activities in ischemic stroke, including neuroprotection [ 118 ], neuroplasticity [ 119 ], and vascular remodeling [ 120 ]. Several studies have shown that neurotrophic factors can be a treatment option for ischemic stroke [ 121 , 122 , 123 ].…”
Section: Applications Of Plga-based Nanostructures In Drug Delivery A...mentioning
confidence: 99%
“…Endocardial cells, which line the atrial and ventricular chambers, are essential for preserving the heart's inner lining integrity and play a role in the creation of embryonic heart valves 16 . Furthermore, cardiac neurons, which are part of the heart's intrinsic neural system, operate autonomously to control heart rate, rhythm, and contractile force, assuring coordinated cardiac activity 17 . Recent imaging studies, reveal their elaborate positioning intertwined with cardiomyocytes within the myocardium 18 .…”
Section: Cardiac Physiologymentioning
confidence: 99%
“…16 Furthermore, cardiac neurons, which are part of the heart's intrinsic neural system, operate autonomously to control heart rate, rhythm, and contractile force, assuring coordinated cardiac activity. 17 Recent imaging studies, reveal their elaborate positioning intertwined with cardiomyocytes within the myocardium. 18 Disregulation of intrinsic cardiac neuron activity can lead to diseases such as arrhythmia and may be one of the causes of loss of cardiac function during ageing.…”
Section: Cardiac Physiologymentioning
confidence: 99%